Apple Pomace as a Sustainable Substrate in Sourdough Fermentation - Martău, Gheorghe Adrian; Teleky, Bernadette-Emőke; Ranga, Floricuţa; Pop, Ioana Delia; Vodnar, Dan Cristian (Frontiers in Microbiology, 2021)
Innovations range from food production, land use, and emissions all the way to improved diets and waste management. Global apple production has amounted to over 87 million tons/year, while 18% are processed, resulting in 20–35% (apple fruit fresh weight) apple pomace (AP). Using modern AP management, integrated knowledge in innovative fermentation demonstrates opportunities for reducing environmental pollution and integration into a circular economy. With this association in view, integrating AP flour during sourdough fermentation increases the nutritional value, highlighting a new approach that could guide innovative fermented foods. In this study, the wheat flour (WF) and AP flour were mixed at different ratios, hydrated with water (1:1 w/v), and fermented using a selective culture of Fructilactobacillus florum DSM 22689 and baker’s yeast (single and co-culture). Sourdough fermentation was monitored and analyzed for 72 h. Results suggested that AP may be an important source of organic acids and fermentable sugars that increase nutritional sourdough value. AP flour addition in WF had a positive effect, especially in fermentations with 95% WF and 5% AP, mainly in co-culture fermentation.